2018
DOI: 10.1002/humu.23677
|View full text |Cite
|
Sign up to set email alerts
|

The role of translation elongation factor eEF1 subunits in neurodevelopmental disorders

Abstract: The multi‐subunit eEF1 complex plays a crucial role in de novo protein synthesis. The central functional component of the complex is eEF1A, which occurs as two independently encoded variants with reciprocal expression patterns: whilst eEF1A1 is widely expressed, eEF1A2 is found only in neurons and muscle. Heterozygous mutations in the gene encoding eEF1A2, EEF1A2, have recently been shown to cause epilepsy, autism, and intellectual disability. The remaining subunits of the eEF1 complex, eEF1Bα, eEF1Bδ, eEF1Bγ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 97 publications
0
60
0
Order By: Relevance
“…Whether the variant proteins impact mRNA stability and/or translation is not yet known. Mutations in the genes encoding the translation elongation eEF1 complex subunits and valyl-tRNA synthetase have also been identified as causes of NDD [100], together expanding our initial focus on mRNA decapping and translation initiation to mRNA deadenylation and translation elongation. Of particular note, a recent large-scale parent-offspring trio study of more than 30 000 affected children with developmental disorders included modeling approaches which suggested that more than 500 novel disease genes remain to be discovered [101].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the variant proteins impact mRNA stability and/or translation is not yet known. Mutations in the genes encoding the translation elongation eEF1 complex subunits and valyl-tRNA synthetase have also been identified as causes of NDD [100], together expanding our initial focus on mRNA decapping and translation initiation to mRNA deadenylation and translation elongation. Of particular note, a recent large-scale parent-offspring trio study of more than 30 000 affected children with developmental disorders included modeling approaches which suggested that more than 500 novel disease genes remain to be discovered [101].…”
Section: Discussionmentioning
confidence: 99%
“…One cannot exclude that the specific localization of subunits may be associated with these diseases. The potential involvement of eEF1B in neurodevelopmental disorders was recently reviewed (McLachlan et al, 2019).…”
Section: Are Non-canonical Functions Of Eef1b Subunits Associated Witmentioning
confidence: 99%
“…Actually, translation is a fundamental cellular process which seems to be essential for normal brain development and function. In this respect, McLachlan et al highlight the possible pathogenic role of defective translation by describing the mutations involved so far in NDD in the eukaryotic elongation factor 1 (eEF1) complex, complex which contains the subunit eEF1Bα encoded by EEF1B2 gene . Because all eEF1 subunits have been shown to be enriched in proteomic studies of postsynaptic densities, the dysfunction of the eEF1 complex is supposed to have a consistent role with defective memory and learning and, consequently with NDD.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Reference . Mutations in genes encoding some subunits of the eEF1 complex (marked with an asterisk) have been reported at the heterozygous or homozygous state within patients with neurodevelopmental disorders [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%